PRAKTIK PERTUKARAN UANG JEMPUTAN DALAM PERKAWINAN ORANG PARIAMAN DI KECAMATAN MEDAN AREA KOTA MEDAN - Mutmainnah, Mutmainnah; Ritonga, Sakti; Ismail, Ismail (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
The focus of the problem in this study is how is the practice of exchanging pick- up money in pariaman marriages in the city of Medan and the social status of men whose nominal amount is determined based on the agreement of the two parties who consider each other until both parties agree on the nominal to be given to the man -man. This tradition can be changed or changed by deliberation. With the development of the times, this tradition is no longer as strict as it used to be, which requires the woman to give a sum of money to the man's family in accordance with the degree or social status in terms of education, work and income owned by the man. The method used in this research is descriptive qualitative research method. Data collection techniques were carried out using in- depth interviews, observation, and documentation. Data collection techniques were carried out by surveying directly to the research location in the village of Tegal Sari 1 and also from several sources of literature studies. Data were analyzed using social exchange theory according to Levi-Strauss. The results showed that the practice of pick-up money in Tegal Sari 1 Village, Medan Area District, Medan City, did not always follow customary rules but was adjusted to the needs and consensus of the family who carried out the exchange process. For example, in Pariaman, there is cello money for ninik mamak, but in the city of Medan, there is none because this depends on the agreement of both parties so as not to burden the women. Some people think that pick-up money is something that is important in relation to preserving customs, but there are also those who refuse to give pick-up money because it is considered unethical. Then, it seems that the provision of pick-up money in the context of the Minang Pariaman overseas in Medan city is largely determined by the social status of men, the higher the social status the man has, the greater the nominal pick-up money. Giving this pick-up money does not include the dowry, but this is the cost incurred by the woman to bring a man to enter the woman's family.